2016
DOI: 10.4081/pmc.2016.117
|View full text |Cite
|
Sign up to set email alerts
|

Meckel’s diverticulum and bowel obstruction due to phytobezoar: a case report

Abstract: Meckel's diverticulum is a common anomaly of the gastrointestinal tract. The most common complications of Meckel's diverticulum are inflammation, bleeding and obstruction. We present a 12-year-old boy with bowel obstruction due to phytobezoar in a Meckel's diverticulum. We describe diagnostic difficulties and our surgery approach comparing it to the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
3
3
0
3
Order By: Relevance
“…In the literature, Meckel's diverticulum accompanying bezoar was reported in several cases during childhood and it was reported that it was mostly of the phytobezoar type. One of them was Meckel's diverticulitis, accompanied by phytobezoar in a 12-year-old patient reported by Gasparella et al [13]. Similarly, in the present study, phytobezoar presented at the Meckel's diverticulum in one case and also accompanied Meckel's diverticulitis.…”
Section: Discussionsupporting
confidence: 82%
“…In the literature, Meckel's diverticulum accompanying bezoar was reported in several cases during childhood and it was reported that it was mostly of the phytobezoar type. One of them was Meckel's diverticulitis, accompanied by phytobezoar in a 12-year-old patient reported by Gasparella et al [13]. Similarly, in the present study, phytobezoar presented at the Meckel's diverticulum in one case and also accompanied Meckel's diverticulitis.…”
Section: Discussionsupporting
confidence: 82%
“…More rarely, bezoars may appear primarily in the small intestine, causing intermittent or permanent intestinal obstruction. In these cases, intestinal motility is significantly disturbed by pathological entities, such as diverticuli, strictures or neoplasms [41,42].…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…При этом наиболее часто встречается инвагинация и заворот кишок [5]. Возникновение непроходимости тонкой кишки из-за фитобезоара в дивертикуле Меккеля является редким состоянием и описано в литературе в единичных случаях [11,12,13].…”
Section: Discussionunclassified
“…Так во всех описанных случаях ОКН из-за фитобезоара дивертикула Меккеля выполнялась резекция участка кишки с дивертиккулом и наложением межкишечного анастомоза или дивертикулэктомия [11,12,13]. Большинство случаев, описанных в литературе, были обработаны с помощью открытой лапаротомии.…”
Section: Discussionunclassified
See 1 more Smart Citation